Active hydrogen evolution through lattice distortion in metallic MoTe2. (24th March 2017) - Seok, Jinbong; Lee, Jun-Ho; Cho, Suyeon; Ji, Byungdo; Kim, Hyo Won; Kwon, Min; Kim, Dohyun; Kim, Young-Min; Oh, Sang Ho; Kim, Sung Wng; Lee, Young Hee; Son, Young-Woo; et al.
Abstract: Engineering surface atoms of transition metal dichalcogenides (TMDs) is a promising way to design catalysts for efficient electrochemical reactions including the hydrogen evolution reaction (HER). However, materials processing based on TMDs, such as vacancy creation or edge exposure, for active HER, has resulted in insufficient atomic-precision lattice homogeneity and a lack of clear understanding of HER over 2D materials. Here, we report a durable and effective HER at atomically defined reaction sites in 2D layered semimetallic MoTe2 with intrinsic turnover frequency (TOF) of 0.14 s −1 at 0 mV overpotential, which cannot be explained by the traditional volcano plot analysis. Unlike former electrochemical catalysts, the rate-determining step of the HER on the semimetallic MoTe2, hydrogen adsorption, drives Peierls-type lattice distortion that, together with a surface charge density wave, unexpectedly enhances the HER. The active HER using unique 2D features of layered TMDs enables an optimal design of electrochemical catalysts and paves the way for a hydrogen economy.